Pengaruh Rasio Keuangan Pada Harga Saham Perusahaan Sektor Pertambangan pada Periode ISSI 2019-2023 - maulana, iqbal; Andni, Riyan (Jurnal Ilmiah Ekonomi Islam, 2024)
Mining has an important role in the Indonesian economy because it provides raw materials needed for various including infrastructure development, manufacturing consumer goods, and providing energy. The aim of this research is to determine and test the relationship between share prices of mining sector business actors in the Indonesian Sharia Stock Index (ISSI) for the 2019-2023 period with the variables CR, DAR and NPM. during the 2020-2023 period. The type of research used is quantitative research. The data analysis technique is using panel data regression analysis because it combines data between companies (cross section) and over time (time series) using the E-Views version 9 software application. The results of this research show that during the 2019–2023 period, mining sector share prices included in the Indonesian Sharia Stock Index (ISSI) will benefit from the Current Ratio (CR) variable. Meanwhile, in mining sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019–2023 period, the Debt to Asset Ratio (DAR) and Net Profit Margin (NPM) variables have no effect on the stock price variable.